Pregnancy planning among women at postpartum period in a public and a private hospital - doi:10.5020/18061230.2008.p269 - Lucila Coca Leventhal; Kristiane Santos Ferreira Barbosa (Universidade de Fortaleza, 2012)
Purpose: To compare the attitudes of women at postpartum period, from a public (PuH) and a private hospital (PrH), regarding their pregnancy planning and to identify contraceptive methods that failed on use, in order to better direct the assistance at contraception. Methods: It was a descriptive study, held on two hospitals from the city of São Paulo. The data collection occurred in August, 2004, by means of a questionnaire applied to all women at postpartum period of each hospital (83 from PuH and 88 from PrU), comprising 171 interviewed. Statistical analysis was done by absolute frequencies and percentages. Results: Most of the interviewed women from PuH (69.9%; n=58) did not plan their pregnancy, while 83.0% (n=73) of those from PrH did so. The contraceptive methods that mostly caused failure were the pill (27.6%; n=16) and the condom (12.1%; n=7) at PuH; and the Ogino- Knaus method [rhythm method of contraception] (26.6%; n=4) and the pill (13.3%; n=2) at PrH. Conclusions: Pregnancy planning was done by most of the women from PrH; the same not occurring for women from PuH. The contraceptive pill and the condom, at PuH, and the rhythm method and the pill, at PrH, were the contraceptive methods that mostly failed. The accomplishment and disclosure of family planning programs for more deprived people is needed, as well as to favor them easy access to contraceptive methods.